Knowledge and Self-Reported Practice of Insulin Injection Device Disposal among Diabetes Patients in Gondar Town, Ethiopia: A Cross-Sectional Study - Abebe Basazn Mekuria; Begashaw Melaku Gebresillassie; Daniel Asfaw Erku; Kaleab Taye Haile; Eshetie Melese Birru (Journal of Diabetes Research)
Background. Incorrect sharp disposal practices may expose the public to needle-stick injuries. The present study aimed at assessing the knowledge and practice of diabetic patients towards insulin injection device disposal in Gondar town, Ethiopia. Methods. A cross-sectional study was employed on insulin requiring diabetes patients who visited the diabetes clinic at Gondar University Referral Hospital (GURH) from February 1 to March 28, 2016. Frequencies, percentages, and ANOVA (analysis of variance) and Student’s t-test were used to analyze variables. Results. About half of the participants (49.5%) had poor knowledge towards safe insulin injection waste disposal. More than two-thirds (80.7%) of respondents had poor practice and 64.3% of respondents did not put insulin needle and lancets into the household garbage. 31% of respondents threw sharps on street when they travel outside. Respondents living in urban areas had a higher mean of knowledge and practice score than those who live in rural area. Conclusions. This study revealed that knowledge and practice of diabetic patients were low towards safe insulin injection waste disposal in study area. Healthcare providers should also be aware of safe disposing system and counsel patients on appropriate disposal of used syringes.